2015
DOI: 10.1021/acs.organomet.5b00788
|View full text |Cite
|
Sign up to set email alerts
|

Aryldihydroborane Coordination to Iridium and Osmium Hydrido Complexes

Abstract: A series of iridium dihydroborate complexes [(tBuPOCOP)­IrH­(κ2-H2BHR)] (tBuPOCOP = κ3-C6H3-1,3-[OPtBu2]2; R = Mes = 2,4,6-Me3C6H2; R = Dur = 2,3,5,6-Me4C6H) and [LIrH­(κ2-H2BHDur)] (L = tBuPCP = κ3-C6H3-1,3-[CH2PtBu2]2, L = η5-C5Me5) and an osmium dihydroborate compound [OsH­(κ2-H2BHDur)­(CO)­(PiPr3)2] have been prepared by using two different synthetic strategies. The first approach is based on direct borane coordination to the metal center, whereas the second is based on a salt-elimination protocol using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…Radius, Braunschweig, et al discussed the limiting structural motifs for complexes of [R 2 BH 2 ] − fragments with transition metals (Chart ). They argued that a more Lewis acidic boron center favors structural type A (κ 2 -dihydroborate) over B (σ-B–H complex of a metal hydride), whereas a more electron-rich metal would favor the higher valence type C (boryl/dihydride). It should be noted that type B may correspond to two degenerate forms ( B and B′ ), which may average out to a more symmetric structure: for example, by NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Radius, Braunschweig, et al discussed the limiting structural motifs for complexes of [R 2 BH 2 ] − fragments with transition metals (Chart ). They argued that a more Lewis acidic boron center favors structural type A (κ 2 -dihydroborate) over B (σ-B–H complex of a metal hydride), whereas a more electron-rich metal would favor the higher valence type C (boryl/dihydride). It should be noted that type B may correspond to two degenerate forms ( B and B′ ), which may average out to a more symmetric structure: for example, by NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The 11 B NMR spectrum of 11 showed a broad signal at δ =21.1 ppm and the 1 H NMR spectrum revealed signals at δ =−19.83 and −6.37 ppm for terminal (Ir‐bound) and bridging hydrides, respectively, along with a broad peak at δ =8.47 ppm for the terminal B−H. The solid‐state structure of 11 , as shown in Scheme , exhibits a tetrahedral arrangement of the boron center, and the Ir−B distance (2.237(3) Å) is similar to other related iridium dihydroborate systems, such as [( t BuPCP)IrH(κ 2 ‐H 2 BHDur)], (2.283(2); t BuPCP: κ 3 ‐C 6 H 3 ‐1,3‐[CH 2 P t Bu 2 ] 2 ) [(Cy 3 P) 2 Ir(H) 2 (κ 2 ‐H 2 BH⋅NMe 3 )][B m Fxyl 4 ], (2.207(7)), and [(SIMes) 2 Ir(H) 2 (κ 2 ‐H 2 BH⋅NMe 2 H)][B m Fxyl 4 ] (2.21(4) Å; SIMes: 1,3‐bis(2,4,6‐trimethylphenyl)imidazolidin‐2‐ylidene).…”
Section: Resultsmentioning
confidence: 99%
“…[10] Even thougho xidative addition of the BÀHb ond of (RO) 2 BH to metal centers is facile, [11] there are few examples of oxidative addition of the BÀHb onds of dihydroboranes [12] which in most cases result in relativelys table k 2 -bis(s)-borane complexes, preventingt he oxidative addition of the BÀHb onds. [13] Nevertheless, the oxidative addition of both BÀHb onds of ad ihydroborane ([MesBH 2 ] 2 )w as achieved by Alcaraz, Sabo-Etienne,a nd co-workersi nt he synthesis of ab orylene complex using the ruthenium-dihydrogen complex [Ru(PCy 3 ) 2 HCl(H 2 )]. [14] The extensive work on both transition-metal-bound and metal-free borylenes has suggested that addition of further (usuallya liphatic)g roups to boron-bound aryl units is ap rerequisite for borylene formation.…”
Section: Introductionmentioning
confidence: 99%
“…A hydrido cobalt intermediate as a possible C–H bond activation product in the study of selective C–F/C–H bond activation of C 6 F 5 H with Co­(PMe 3 ) 4 was proposed on the basis of the observation of in situ IR and 1 H NMR spectra, but an experiment to isolate the hydrido cobalt intermediate also failed . Except for the C–H activation pathway, direct reduction is also feasible in synthesizing metal hydrides according to refs and . The reaction of bromopentafluorobenzene with Fe­(PMe 3 ) 4 in diethyl ether at room temperature gave a red solution.…”
Section: Resultsmentioning
confidence: 99%